Unusual primary sphenoid adenoid cystic carcinoma: the importance of combined CT and MR evaluation (Bangladesh Journal of Medical Science, 2016)
Objective: To report a diagnostic challenge of primary sphenoid adenoid cystic carcinoma. Case summary: A 60-year-old premorbid healthy lady presented with progressive deterioration of visual acuity of the left eye associated with diplopia, left epiphora and left ear blockage for two weeks duration. Examination revealed a non perception of light (NPL) of the left eye with left abducent nerve palsy. The nasoendoscopic findings were unremarkable. Initial computed tomography of the brain and paranasal sinus showed a large clivus tumor with intracranial extension while subsequent magnetic resonance detected the epicenter of the tumour appeared to be in the sphenoid sinus with extension to the surrounding structures. A transeptal transsphenoidal biopsy was done reported as mixed pattern adenoid cystic adenocarcinoma. Discussion: Primary sphenoid adenoid cystic carcinoma is an extremely rare slow growing malignancy with non-specific clinical symptoms. The neuro-ophthalmology symptoms are the main presentation. Combined computed tomography and magnetic resonance images are essential in establishing differential diagnosis and to delineate the extent of this disease. Combined modality of surgery and postoperative radiation for adenoid cystic carcinoma has proven better results. Conclusions: Primary sphenoid adenoid cystic carcinoma poses a diagnostic challenge clinically. Combined radiological characteristic from computed tomography and magnetic resonance images are essential to aid the diagnosis.Bangladesh Journal of Medical Science Vol.15(2) 2016 p.297-302